Investigation of the immunostimulatory effects of some New Zealand honeys and characterization of an active component : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Technology in Food Technology at Massey University, Albany, New Zealand - Gannabathula, Swapna; Gannabathula, Swapna (Massey University, 2010)
Medicinal use of honey has re-emerged recently indicating that honey accelerates wound healing activity. Honey has been shown to stimulate TNF-α production from monocytes and macrophages which is apparently correlated with a high molecular weight fraction, and not lipopolysaccharide (LPS, an immunostimulatory endotoxin) levels. Cytokine production by honey has been attributed to the endotoxin content. The aim of this study was to investigate the ability of Comvita sourced honeys to elicit a TNF-α cytokine response from acute monocytic leukemia (THP-1) cells as well as identify the responsible component. Five honey samples were used together with sugar and methylglyoxal controls. The samples were incubated with THP-1 cells, with and without LPS. After incubation, the cell culture supernatants were collected and TNF-α was measured by the enzyme-linked immune sorbent assay (ELISA). The most active honey samples were further heat-treated to remove enzyme/protein/peptide-like stimulation; the samples were treated with polymixin [i.e. polymyxin] B (PmB) to remove LPS-like stimulation and not protein fraction. The samples were then filtered by molecular weight centrifugal filters to separate constituents according to their size and the fractions were re-analysed. All five honey samples in the absence of LPS stimulated TNF-α release from THP-1 cells, whereas untreated, sugar- and methylglyoxal-treated cells did not. The cytokine production was partially inhibited by heating, but mostly by PmB. In the filtered honey samples, the activity was observed in the >30 kDa fraction. These results suggest that the activity may be associated with one or more components which are partially heat-labile, LPS-like stimulated with a high molecular weight. Further, honey samples were analyzed for the concentration of LPS present. The tests revealed that the cytokine stimulation was higher than would be expected from the concentration of LPS present in the honey. The possibility that this component was a plant-derived ß-glucan, which is known to have LPS-like activity and can interfere with detection of LPS in the LAL assay, was investigated. Subsequent analyses confirmed the presence of arabinogalactan, a large complex carbohydrate. The data presented in this study suggests that arabinogalactans in honey may stimulate inflammatory responses and the release of cytokines that are crucial in regulating wound- healing. This heralds a significant advancement in the usage and understanding of medicinal honey.
Keywords: Medicinal honey; Tumor necrosis factor-alpha; Cytokines